Peran Modal Intelektual dalam Keunggulan Bank Syariah di Indonesia - Rahmadhani, Annisa; Widyaningsih, Meilana (Universitas Islam Negeri Alauddin Makassar, 2024)
This study aims to determine the influence of Intellectual Capital on Profitability in Sharia Commercial Banks in Indonesia. The population used in this research is the annual financial reports of Islamic banks registered with Sharia Commercial Banks (BUS) for 2019-2023. The number of samples used in this research was 11 samples. The type of data used in this research is quantitative research, using secondary data with financial reports. The analysis tool used is SPSS 23.0. The data analysis used is in the form of classical assumption tests and multiple linear regression analysis. The results of this test show that simultaneously Intellectual Capital (VACA, VAHU, and STVA) has an effect on profitability (ROA) of 72.1%. Partially, it indicates that VACA and VAHU have a significant impact on bank profitability (ROA), because the significant value of these two variables is <0.05. Meanwhile, STVA does not have a significant effect on profitability (ROA), this is because the significant value of STVA is > 0.05.